PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMA NEGERI 1 KERITANG KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - AGUSSAIRI, AGUSSAIRI (Mikraf: Jurnal Pendidikan, 2023)
The success or failure of a school depends on the leadership of the principal, the background factors include, among others, the role of leadership that is not good in developing the quality of education such as "Supervision and facilities and infrastructure that are not yet optimal. The formulation of the problem of this thesis is how the role of the principal in improving the quality of education. What are the results of the principal's leadership role in improving the quality of education. This study uses a qualitative descriptive analytical approach. Data was collected by using observation, interview and documentation techniques. Determination of research subjects using snowball sampling technique. The purpose of this study was to determine the role of the principal's leadership in improving the quality of education. To find out the improvement of the leadership quality of school principals in the quality of education. To find out the results of the leadership role of the principal in improving the quality of education. The results showed that: 1. The leadership role of the principal in SMA Negeri 1 Keritang became a central element in determining the direction of school success and the leadership of the principal optimally, so that the principal had more time to be in the school environment 2. Improving the quality of the principal paying attention to the community the school makes it a vision and mission, compiles programs (prota, promissory notes), implements what has been arranged, and evaluates, and facilitates the interest of students' talents with extracurricular activities and improving the quality of facilities and infrastructure that has not been maximized. 3. Most graduates are able to continue on to quality public and private universities.